2006
DOI: 10.1517/13543784.15.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of central precocious puberty

Abstract: The problems of central precocious puberty (CPP) are serious enough to the patient to deserve treatment. There is a general consensus among paediatric endocrinologists that the treatment of true CPP (i.e., in children young enough to have a formal diagnosis) is indicated in many cases. In children with modestly early puberty who are not fulfilling the diagnostic criteria, this is not the case. The treatment of choice is a gonadotropin-releasing hormone (GnRH) analogue. Prolonged analogues are more effective th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…The decision to discontinue treatment should be taken jointly by the endocrinologist, the child and the parents. The suppression of puberty seems to be reversible on cessation of treatment and reproductive function seems to be unaffected . Pubertal manifestations generally reappear within months of GnRHa treatment being stopped, with a mean time to menarche of 16 months …”
Section: Central Precocious Pubertymentioning
confidence: 99%
“…The decision to discontinue treatment should be taken jointly by the endocrinologist, the child and the parents. The suppression of puberty seems to be reversible on cessation of treatment and reproductive function seems to be unaffected . Pubertal manifestations generally reappear within months of GnRHa treatment being stopped, with a mean time to menarche of 16 months …”
Section: Central Precocious Pubertymentioning
confidence: 99%
“…The study was designed as a randomized open stratified multicenter study involving 20 pediatric clinics in Sweden. It was found that the GH addition gave a small but significant FH increase for the combined GH+GnRHa treatment group as a whole [24,25,26]. It appeared that not all patients would need addition of GH in order to attain satisfactory FH, but only a selected group.…”
Section: Introductionmentioning
confidence: 99%
“…The use of gonadotropin-releasing hormone (GnRH) agonists (GnRHas), colloquially known as puberty blockers, is to suppress puberty and treat gender dysphoria: a sense of misalignment with one's biological sex and gender identity that may occur in transgender and nonbinary (TNB) adolescents. The use of many GnRHas has been proven to be safe and approved by the US Food and Drug Administration in the early 1990s ( 1 ) for the treatment of precocious puberty in adolescents ( 2 ), and reproductive cancers in adults ( 3 ). Therefore, it is important to understand the effect of pausing puberty on the brain and behavioral development during adolescence.…”
mentioning
confidence: 99%